2009
DOI: 10.1080/07357900802570759
|View full text |Cite
|
Sign up to set email alerts
|

Improved Response by Co-targeting EGFR/EGFRvIII and Src Family Kinases in Human Cancer Cells

Abstract: We hypothesized that co-targeting the epidermal growth factor receptor (EGFR) and Src with the EGFR inhibitor gefitinib and the Src inhibitor AZD0530 would increase growth inhibition and impede migration. Cells overexpressing EGFR were more sensitive to gefitinib than cells expressing mutated EGFR or normal levels of wild-type EGFR. Furthermore, cells with mutated EGFR responded to low doses of gefitinib with increased proliferation. AZD0530 was an effective inhibitor of proliferation and migration, irrespecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Therefore, blocking phosphorylation of the site might have therapeutic benefits. AQP5 have been found expressed highly in primary human glioma cells compared with normal tissue, this is in accordance with the study that reported AQPs (such as AQP1 , AQP5 and AQP8 ) have been observed in high-grade tumors of various tissues [29, 30]. It is confirmed that high expression of AQP5 was associated with tumor growth, invasion and metastasis in non-small cell lung cancer [31].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, blocking phosphorylation of the site might have therapeutic benefits. AQP5 have been found expressed highly in primary human glioma cells compared with normal tissue, this is in accordance with the study that reported AQPs (such as AQP1 , AQP5 and AQP8 ) have been observed in high-grade tumors of various tissues [29, 30]. It is confirmed that high expression of AQP5 was associated with tumor growth, invasion and metastasis in non-small cell lung cancer [31].…”
Section: Discussionsupporting
confidence: 88%
“…2A and B). The enhanced effects of combined activation of targeting Src and EGFR signaling pathways are previously reported (6,20,(36)(37)(38). Furthermore, targeting Src in combination with trastuzumab-sensitized trastuzumabresistant cell lines (23), and inhibition of integrin/FAK/ Src pathway overcame lapatinib resistance (24).…”
Section: Discussionmentioning
confidence: 80%
“…44 Decreased c-Src kinase activity resulted in increased sensitivity to EGFR inhibitors in head and neck cancer and epidermoid carcinoma cell lines. 45,46 A recent Phase I/II study has also been published utilizing dasatinib in combination with the EGFR TKI erlotinib in non-small cell lung cancer. 47 Not only was this combination tolerable in patients, but disease control was also observed.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%